Working (longer than) 9 to 5: are there cardiometabolic health risks for young Australian workers who report longer than 38-h working weeks? - Reynolds, A.; Bucks, R.; Paterson, J.; Ferguson, S.; Mori, T.; McArdle, N.; Straker, Leon; Beilin, L.; Eastwood, P. (Springer, 2018)
© 2018 Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: The average Australian working week in middle-aged and older workers exceeds government recommendations. Long working weeks are associated with poor health outcomes; however, the relationship between long working weeks and health in young Australian workers is unknown. Methods: Data were drawn from the 22-year follow-up of the Western Australian Pregnancy Cohort (Raine) Study in Perth, Western Australia. Information was available from 873 young adults about working hours per week, shift work and sleep duration. Blood samples provided measures of cardiometabolic risk (CMR) factors. Results: Almost one-third (32.8%) of young workers reported > 38 h working weeks. This was commonly reported in mining and construction industries for males; health and social assistance, mining and retail trade industries for females. CMR factors including increased waist circumference, higher fasting plasma glucose and reduced HDL cholesterol were associated with > 38 h working weeks. These relationships were not moderated by gender or by BMI for glucose and HDL cholesterol. Total sleep time was significantly lower in both male and female workers reporting > 38 h working weeks, but did not mediate the relationships seen with CMR factors. Conclusions: These findings point to early associations between > 38 h working weeks and CMR risk, and highlight the potential benefit of making young employees aware of the health associations with working arrangements to reduce the longer-term relationships seen with working hours and poor cardiometabolic health in population studies.